(untitled) (CAHIERS MAGELLANES-NS, 2024)
This paper investigated the impact of constructive written feedback upon technical writing competence development in polytechnic students. Technical writing is one important aspect of any type of professional communication; the most students find difficulties in mastering this skill as it often involves something complex with nuances. A mixed-method approach has been utilized here with both quantitative measurements about writing performance as well as qualitative analysis about students' experiences with feedback. Results show: This study was structured and precise; the results obtained would show that students, in a very high percentage, improve significantly in their writing skills, the understand ability of concepts is better with high clarity and coherence, and the number of iterations of feedback processes indicates that students tend to be confident with their writing skills. The study thus stresses the importance of introducing positive feedback mechanisms in technical writing curricula, but it finally comes up with a set of strategies to be applied in teaching educators to improve the outcome of their students' learning and preparation for industry.